Factors Causing Verbal Bullying Behavior in Elementary School Students - Abatan, Fredrich Euricho; Anakaka, Dian L.; Wijaya, R. Pasifikus C. (Universitas Nusa Cendana, 2025)
Bullying is negative behavior carried out by someone who has more power or power over someone who aims to hurt and is carried out intentionally and causes the victim to feel uncomfortable and can occur in several forms, namely verbal, physical and mental. The aim of this research is to analyze the factors that cause verbal bullying behavior in fifth grade students at St. Catholic Elementary School. Yosef Atambua 1 academic year 2023/2024. The research design uses qualitative research with a case study approach. Participants in this research were the perpetrator, victim, peers, perpetrator's parents, teacher and school principal. Data was collected and analyzed using thematic data analysis techniques. From the results of data analysis, it was found that verbal bullying behavior occurred due to several factors behind this behavior, such as the contribution of children, in this case the student who bullied had an angry, aggressive and anti-social nature.